A systematic review of factors affecting choice of otolaryngology as a career in medical students and junior doctors. Issue 10 (19th September 2019) - Mayer, A W; Smith, K A; Carrie, S
Abstract: Background: There is growing concern over a future shortfall in provision of UK otolaryngology consultants. There is a declining rate of applications to otolaryngology specialty training in the UK. Objective: This study aimed to systematically review the literature to establish what factors influence medical students' and junior doctors' decision to pursue a career in otolaryngology. Method: Medline, Embase and PubMed databases were searched in January 2019. Additional manual reference checks of identified literature were performed. Results: Eleven articles were included in the review. Common factors that positively influenced the decision to pursue a career in otolaryngology were exposure to the specialty, positive role models and a good work-life balance. Lack of exposure was a consistent deterrent from pursuing a career in otolaryngology. Conclusion: This review reiterates the need for greater exposure to otolaryngology in the undergraduate curriculum. In addition, mentorship for students with an interest in otolaryngology should be a priority.